Qualified appraisals and qualified appraisers : expert tax valuation witness reports, testimony, procedure, law, and perspective - Devitt, Michael R., 1957-; Sannicandro, Lawrence A., 1979- (Wiley finance, 2017)
"There has been a steady flow of controversies since the IRS issued its regulations on qualified appraisers and qualified appraisals. The IRS has developed a body of law relating to the qualifications needed to satisfy the Government that an appraisal is adequate to support the taxable event on the taxpayer's return. This book discusses elements related to testifying experts and introduces a novel form of expert testimony: hot tubbing. The book identifies the law, analyzes the cases, identifies the problems and provides insight and solutions to help appraisers do work which will be accepted by the IRS"--